Malaysian's level of Standard Operating Procedure (SOP) compliance in the fight against COVID-19 infection during endemic phase / Nur Adila Abdul Yazid … [et al.] - Abdul Yazid, Nur Adila; Mahat, Nurfatihah Farahin; Bakar, Mohd Hilmi; Hassan, Mohd Suffiean (Faculty of Communication & Media Studies, 2022)
A standard operating procedure (SOP) is a set of written instructions that describes the step-by-step process that must be taken to properly perform a routine activity. The goal of this study is to examine if Malaysians are concerned about SOPs during the endemic period and if SOPs have been successful in lowering infection rates among the general population. An online questionnaire with 12 items for demographic section and 16 items was designed in order to evaluate the Malaysia level of standard operating procedure (SOP) compliance in the fight against COVID-19 infection during endemic phase. The study is using the quantitative survey method which involves 306 respondents consisting of the public with various backgrounds by using Google Form platform. There are three main elements designed in this research in order to measure Malaysia's level of standard operating procedure (SOP) compliance in the fight against COVID-19 infection during the endemic phase. All variables were measured through the scale previously used by another researcher and scale of approval from 1 (Strongly disagree) - 4 (Strongly agree). The final result of the research indicates that the level of SOP compliance during endemic is very high (M= 3.70), followed by the level of concern for the public in complying with the SOP is also very high (M=3.27) and the level of effectiveness of SOP compliance is very high (M=3.48).